2023
DOI: 10.1002/ajh.26891
|View full text |Cite
|
Sign up to set email alerts
|

Improved survival of patients with primary plasma cell leukemia with VRd or daratumumab‐based quadruplets: A multicenter study by the Greek myeloma study group

Abstract: We evaluated the efficacy and prognostic impact of bortezomib‐lenalidomide triplet (VRd) or daratumumab‐based quadruplets (DBQ) versus previous anti‐myeloma therapies, that is, bortezomib standard combinations (BSC) or conventional chemotherapy (CT), in a large cohort of patients with primary plasma cell leukemia (pPCL), including those fulfilling the revised diagnostic criteria, that is, circulating plasma cells (cPCS): ≥5%; 110 pPCL patients (M/F: 51/59; median age 65 years, range: 44–86) out of 3324 myeloma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
(96 reference statements)
0
2
0
Order By: Relevance
“…A retrospective multicenter study by the Greek Myeloma Study Group investigated patients with pPCL defined as ≥5% CPCs. They reported that patients who received VRd (bortezomib-lenalidomide-dexamethasone) or daratumumab-based quadruplets had a higher complete response (CR) rate of 41%, with an improved median PFS of 25 months and a median OS not reached in comparison to conventional chemotherapy or best supportive care [ 30 ]. Other groups reported conflicting data regarding the magnitude of the improved outcomes with aggressive regimens, including allogeneic transplantation [ 18 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective multicenter study by the Greek Myeloma Study Group investigated patients with pPCL defined as ≥5% CPCs. They reported that patients who received VRd (bortezomib-lenalidomide-dexamethasone) or daratumumab-based quadruplets had a higher complete response (CR) rate of 41%, with an improved median PFS of 25 months and a median OS not reached in comparison to conventional chemotherapy or best supportive care [ 30 ]. Other groups reported conflicting data regarding the magnitude of the improved outcomes with aggressive regimens, including allogeneic transplantation [ 18 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…10 New agents with novel mechanisms of action should also be investigated in this disease. Daratumumab-containing regimens are increasingly used to treat patients with newly diagnosed primary plasma cell leukaemia, based on promising results from retrospective studies, 23 as well as favourable clinical outcomes in multiple myeloma. 24,25 Ongoing clinical trials (such as NCT0587091 and NCT05219721) are evaluating whether incorporation of T-cell redirecting therapies (eg, CAR T-cell therapy and bispecific antibodies) in the treatment strategy further improves depth of response and survival of patients newly diagnosed with primary plasma cell leukaemia.…”
Section: Discussionmentioning
confidence: 99%
“…Although the prognosis of patients with pPCL has significantly improved with daratumumab-based quadruplets, del17p(+) predicts poor outcome [2].…”
mentioning
confidence: 99%